Teacher Planning and Interactive Decisions Concerning Five Aspects of Teacher Language Use - Saswati, Risna (IKIP Siliwangi, 2025)
The study investigates teacher decision making while planning the lesson and teacher doing classroom instructions. Additionally, the practice is related to teacher language use: teacher talk, teacher questions, teacher use of Indonesian and metalanguage, and teacher corrective feedback. The research method employed is a descriptive qualitative method by using the theories of teacher decision making (Richards, 2007), and teacher language use (Ellis, 2012) for data analysis techniques. The participant of this study is an experienced English lecturer teaching at a university in Jakarta. The result reveals that the teacher makes some decisions in planning the lesson related to her language use based on the students’ capacity, classroom activities, her belief, perception and cognition, and the speaking skills and components. In her instructional teaching, decision making occurs in using her classroom language since she changes some activities. She makes some decisions according to the student’s abilities, classroom activities, culture, and the lesson. The decision making made by the teacher can facilitate opportunities for the learners to engage in classroom interaction and improve their speaking skills.